AI adoption in the enterprise 2022 - Loukides, Michael Kosta (O'Reilly Media, Inc., 2022)
The AI hype is winding down, so where are we now? How far along are most companies in terms of AI adoption? Do they have working applications in production? What tools are they using? What are the biggest bottlenecks? How much has changed since last year, and what does that tell us about the future of AI? If you're curious about the state of AI today, or just want to see how your organization compares to others, check out this new O'Reilly report.